2018
DOI: 10.1590/1518-8345.2601.3031
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of well-being and quality of life in men who underwent radical prostatectomy: longitudinal study

Abstract: Objective:to identify socio-demographic, clinical and psychological predictors of well-being and quality of life in men who underwent radical prostatectomy, in a 360-day follow-up. Method:longitudinal study with 120 men who underwent radical prostatectomy. Questionnaires were used for characterization and clinical evaluation of the participant, as well as the instruments Visual Analog Scale for Pain, The Ways of Coping Questionnaire, Hospital Depression and Anxiety Scale, Satisfaction with Social Support Scale… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 74 publications
0
8
0
4
Order By: Relevance
“…Patients often suffer from the symptoms and side effects of treatments alone, and inadequate support leading to more severe depression [ 26 ]. Past research has revealed that family support is associated with emotional-focused coping and good quality of life [ 27 ]. Also, exercise intervention, intensive nutrition, and stress-relief practices have a significant effect on the melancholy of cancer patients [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…Patients often suffer from the symptoms and side effects of treatments alone, and inadequate support leading to more severe depression [ 26 ]. Past research has revealed that family support is associated with emotional-focused coping and good quality of life [ 27 ]. Also, exercise intervention, intensive nutrition, and stress-relief practices have a significant effect on the melancholy of cancer patients [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…It is possible that this association may occur because previously anxious patients are prone to misunderstand information offered by the healthcare team 22 . Thus, rather than understand that a given complication is possible, the individual internalizes the information as if the complication will actually occur 23,24 . It is therefore important for the healthcare team to identify anxious patients in the preoperative period before offering details regarding the procedure to quell doubts and enable the information to be truly beneficial.…”
Section: Discussionmentioning
confidence: 99%
“…In this context, conjugal satisfaction was established as a predictor for the variables presented. 19 It is believed, therefore, that, in the possession of this knowledge, nurses should redirect their practice better, seeking to act on the risk factors and the social determinants of health, with a focus centered on male education for adopting more healthy. It is also important to emphasize the need for the nursing team to consciously and critically perform strategies for the prevention and screening of prostate cancer so that men do not undergo early intervention.…”
Section: Discussionmentioning
confidence: 99%